Continuous Management of a Retail Product Category - Pospíšilová, Lucie; Koudelka, Jan; Tahal, Radek, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The aim of the thesis is to describe the Czech retail industry and the practice used in the category management. The work compares and evaluates the current state of the ice-cream category management in different retail chains and recommends changes for the next ice-cream season for one of the retailers. The description of the retail industry and the introduction set the background for the thesis and the explanation of the continuous category management provides the framework for the analysis. The empirical part conducts the category planning step by step. The key parts are category assessment and category scorecard, which benchmark different stores in terms of assortment, display, price, and promo. Finally recommendations and conclusions are derived from the analysis to improve the category performance.
Vedoucí práce: Jan Koudelka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses